A Letter Invited on a Trip: Practice of Dealing with Complaints in Soviet Lithuania - Marcinkevičienė, Dalia (Genocidas ir rezistencija, 2007)
In Soviet post-war society many letters / complaints which had little to do with ideology or police were written. People who wrote those complaints did not intend to report or punish anyone. Rather they were concerned only with solving their own everyday life problems and improve it. Purely personal interests of those who wrote letters show that messages like those were simply grievances about everyday life. Often complaints became an officially legal form of blat (connections) and were promoted by those who did not have any strong social connections. Those who used blat resorted to personal connections, while the writers of complaints used official institutions. The authorities in Soviet Lithuania encouraged those who wrote complaints. Soviet citizens who saw some evil in society were urged to address higher institutions of power. The 2 August 1958 resolution passed by the Central Committee of the USSR “On serious shortcomings in dealing with ordinary people’s letters, grievances and reports” was to encourage people to complain about social evil. It attracted attention to the importance of the control dealing with grievances. One of the most important party and government chains, which was to ensure people’s confidence to write letters was the State Control Committee of the Council of Ministers of the Central Committee of the Lithuanian Communist Party.
Keywords: Soviet Lithuania; Soviet society; Soviet ideology